Open Distance and e-Learning: Ethiopian Doctoral Students’ Satisfaction with Support Services - Aberra, Tsige GebreMeskel; Davids, Mogamat Noor (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2022)
This study assessed students’ level of satisfaction with the quality of student support services provided by an open distance e-learning (ODeL) university in Ethiopia. The target population was doctoral students who had been registered at the ODeL university for more than a year. To conduct a quantitative investigation, data were collected by means of a 34-item six-dimensional standardized questionnaire. Data analysis methods included linear as well as stepwise regressions. Using the gaps model as the theoretical framework, findings showed that the doctoral students were dissatisfied with four aspects of the student support services, namely supervision support, infrastructure, administrative support, and academic facilitation. In contrast, students were satisfied with the corporate image (reputation) of the ODeL university. For this ODeL university to play an effective role that coheres with the country’s socio-economic development plan, more attention should be given to the provision of supervision support, as there was strong dissatisfaction with this. The university could also build on or leverage aspects of their corporate image, for which there was strong satisfaction. Doing so will help the university make ongoing contributions and strengthen its commitment to the field of higher education and human capacity development in Ethiopia.